1993
DOI: 10.2172/10128343
|View full text |Cite
|
Sign up to set email alerts
|

CO{sub 2}/sand fracturing in Devonian shales

Abstract: This report was prepared as an account of work sponsored by an agency of the _ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…According to King [96], Arnold [11] and Campbell et al [34], only 25-50% of water-based fracturing fluid can be recovered and recovery takes extensive time (months or years). This issue can be minimized by using CO 2 -based fracking fluid, as the average clean-up time for CO 2 -based fracturing fluid is as short as several days [35,96]. In addition to its small molecular size, large compressibility, and high diffusion rate, the phase changes of CO 2 from super-critical/liquid to gas while it moves upward due to the reduction of pressure also significantly reduce the time required for residual CO 2 to move back to the surface.…”
Section: Minimization Of Issues Related To Residual Fluidsmentioning
confidence: 99%
“…According to King [96], Arnold [11] and Campbell et al [34], only 25-50% of water-based fracturing fluid can be recovered and recovery takes extensive time (months or years). This issue can be minimized by using CO 2 -based fracking fluid, as the average clean-up time for CO 2 -based fracturing fluid is as short as several days [35,96]. In addition to its small molecular size, large compressibility, and high diffusion rate, the phase changes of CO 2 from super-critical/liquid to gas while it moves upward due to the reduction of pressure also significantly reduce the time required for residual CO 2 to move back to the surface.…”
Section: Minimization Of Issues Related To Residual Fluidsmentioning
confidence: 99%
“…In the early 1990s the United States DOE started to introduce liquid CO 2 fracturing into vertical Devonian shale wells in eastern Kentucky (Yost et al 1993). Two-stage stimulations with CO 2 /sand, GN 2 , and N 2 foam/sand were performed in four, seven, and four gas wells within a distance of 20 km, respectively (Yost et al 1994).…”
Section: Co 2 Fracturingmentioning
confidence: 99%
“…Note that GN 2 treatments did not place sand proppants in fractures. A follow-up review updated the 5-year production data for the seven wells (11 stages) stimulated by CO 2 /sand, the nine wells (17 stages) by GN 2 , and the five wells (9 stages) by N 2 foam/sand (Mazza, 2001) from those previously reviewed by Yost et al (1993Yost et al ( , 1994. It demonstrated that the ratio of cumulative production per stage from CO 2 /sand stimulations to GN 2 and N 2 foam/sand stimulations had increased from 1.9 and 4.9 to 3.0 and 6.5 times over the 5-year period, respectively.…”
Section: Co 2 Fracturingmentioning
confidence: 99%
“…Several field operations in the Devonian shale reservoirs demonstrated that fracturing with low injection rates can open the NF pathways, whereas high injection rates create HFs [34,35]. Although low injection rates (2.4-3.2 m 3 /min) in shale reservoirs successfully opened NFs, they did not develop lasting gas rates, even with large fracturing volumes.…”
Section: Introductionmentioning
confidence: 99%